INTERVAL KEPERCAYAAN BAYESIAN UNTUK RATAAN DISTRIBUSI POISSON DENGAN MENGGUNAKAN DISTRIBUSI JEFFREY SEBAGAI DISTRIBUSI PRIOR - Mulyati, Sri (Jurnal Ilmiah AdMathEdu, 2011)
Suppose X Poisson distributed with parameter ?. This journal aims to determine the confidence interval for the average Bayesian Poisson distribution with parameter ?. The research method used in this discussion is a method of literary study. Prior distributions are used to determine the posterior distribution is the distribution of Jeffrey. To facilitate the calculation of confidence intervals of the Bayesian 100 (1 - ?)% for the parameter ? used MATLAB program. The performance of the confidence interval for the average Bayesian Poisson distribution in a test using simulated data. As an example of the application was applied to stop the Trans Jogja Kusuma Negara 3.